PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA DOSEN DI AKADEMI SEKRETARI DAN MANAJEMEN ARIYANTI - Rizzky Rustiadi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
ABSTRACT The Influence of Transformational Leadership On Lecturer Performance (Research Locus at Ariyanti Academy of Secretary and Management, Bandung City). This research was conducted at the Ariyanti Academy of Secretariat and Management Campus, Bandung. Where the locus of this research is where the author works. In this study, the researchers tried to carry out a study that was associated with current technological developments. . Current technological developments have entered the era of the industrial revolution where almost all work activities use digital access. The research method used is descriptive analysis, with a population of 50 people and all of them are used as respondents (Survey). The data analysis technique used is descriptive analysis technique. The result of his research is that Transformational Leadership at the Ariyanti Academy of Secretariat and Management is categorized as quite good. Lecturer performance is categorized as quite good. This can be seen from the criteria for achieving a score of 3.14. Keywords: Leader, Transformational Leadership, Lecturer Performance.